DETERMINANTS AFFECTING THE DEPRESSION OF INFARCTION POST STROKE PATIENTS IN (SAIFUL ANWAR HOSPITAL MALANG) - Munir, Badrul; Nasution, Arief Alamsyah; Purnamasari, Yeni (Malang Neurology Journal, 2016)
Background. Stroke is a functional disorder of the brain that occurs suddenly with signs and symptoms ofÂ both focal and global clinical lasting more than 24 hours, or can lead to death due to circulatory disorders of the brain. Stroke ranks third leading cause of death in Indonesia. Someone with stroke will leading mood disruption that would cause a depression. Objective. To determine the effect on depression of stroke infarction.Methods. The study used descriptive analytic cross-sectional study. 42 samples was selected by consecutive method. The distribution of the sample are 18 males and 24 females, 23 samples below 60 years and 19 samples over 60 years, 13 samples had duration of suffering a stroke less than 6 months and 29 samples above 6 months. The independent variables in this study were age, sex, and duration of suffering a stroke, while the depression is the dependent variable. Depression was assessed using the Hamilton Depression Rating Scale (HDRS). Results. The results used logistic regression test obtained value of (p = 0.021) is significant in age.Conclusion. The age is the determinant affecting the quality of life after stroke infarction.